2022
DOI: 10.1186/s12909-022-03507-3
|View full text |Cite
|
Sign up to set email alerts
|

Does peer teaching improve academic results and competencies during medical school? A mixed methods study

Abstract: Background This study investigates the impact of Peer-Assisted Learning (PAL) in clinical skills on peer teachers’ academic scores and competencies; however, controversy remains on this topic, and concrete evidence on its impact lacking. Methods We performed a mixed methods study combining a retrospective cohort study with a modified Delphi survey. Peer teachers and Skills Lab faculty members participated in this study. A validated questionnaire, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
(25 reference statements)
1
11
0
1
Order By: Relevance
“…Many suggested interactive teaching sessions for vaccine education, such as role play and simulated patients. Studies have shown that practical teaching is more effective than lectures in facilitating the learning process and improving knowledge outputs [20,[50][51][52]. In one needs-assessment study, students enjoyed learning from flipped classroom and case-based formats, and felt more confident in their approach towards vaccine-related discussions [53].…”
Section: Student-suggested Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many suggested interactive teaching sessions for vaccine education, such as role play and simulated patients. Studies have shown that practical teaching is more effective than lectures in facilitating the learning process and improving knowledge outputs [20,[50][51][52]. In one needs-assessment study, students enjoyed learning from flipped classroom and case-based formats, and felt more confident in their approach towards vaccine-related discussions [53].…”
Section: Student-suggested Improvementsmentioning
confidence: 99%
“…Peer-teaching and role play may be advisable approaches. In several countries, peer teaching at undergraduate medical schools has been encouraged as part of the formal curriculum to help students train as educators and supervisors in anticipation of their roles as future doctors [50].…”
Section: Student-suggested Improvementsmentioning
confidence: 99%
“…Their analyses revealed that this performance was not due to their participation in PAL per se but reflected a selection bias: The better-performing students were the students who applied for the peer teaching program. The finding was corroborated by comparing peer teachers to a group of equally well-performing fellow students, eliminating the differences between peer-teaching students and nonpeer-teaching students 21 . Many studies have shown the benefits of social unity as a significant player in peer-assisted learning.…”
Section: Discussionmentioning
confidence: 85%
“…by different researchers and the studies have given encouraging results in terms of better acquisition of knowledge and performance in assessments. 1,3,[5][6][7] In peer teaching, the general fear associated with committing a mistake in a teacher-student setting is significantly reduced. 4,5 In other words, they feel comfortable and safe to learn from their peers without being afraid of worrying about the consequences, if they commit a mistake.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] This entire process is not only useful for the students but even for the teachers as they gain insights on different ways a topic can be taught, especially keeping in mind how the students of the current generation learn. 6,7 Considering the fact that medical education is complex, wherein students are expected to learn multiple competencies, learning media occupy a crucial place as they aid the students to acquire the intended learning competencies expected of a medical graduate. 8 The need of the hour is to employ a combination of learning media that will neutralize the monotony linked with conventional media and will give students a chance to actively engage, promote better retention, and stay motivated in the learning process.…”
Section: Introductionmentioning
confidence: 99%